IMPROVING ENGLISH SPEAKING BY USING ROLE PLAY TO SEVENTH GRADE OF SMPN 8 CIMAHI IN ACADEMIC YEAR 2016/2017 - Andri Abdul Basit (PROJECT (Professional Journal of English Education), 2018)
This study is conducted in order to develop students’ speaking at first grade students of SMPN 8 Cimahi through role play activities. This study is related to the result of a preliminary study showed that the students were still poor in English speaking skill; especially in giving interpersonal response. This study used a Classroom Action Research (CAR) which is conducted to solve the students’ problem in English Speaking. The Classroom Action Research (CAR) was done based on Kemmis and McTaggart design. The writer did two cycles in which each cycle consists of planning, acting, observing, and reflecting.The data were gathered through quantitative data. quantitative data were obtained from the students’ speaking score of pretest and posttest and questionnaire. The results of this research showed that the use of Role Playing technique was successful to improve the students’ speaking. Classroom English helped the students to be more familiar with English, The vocabulary and pronunciation practices and role play performances also helped them to enrich their vocabulary knowledge and build their accuracy. Furthermore, Role Play technique was successful to encourage them to practice speaking. Meanwhile, the use of various media could attract their attention during the class. Based on the quantitative data, the students’ mean scores for the speaking skill improved from 8.25 in the pretest to 14.20 in the posttest.